3D Micro‐Extrusion of Graphene‐based Active Electrodes: Towards High‐Rate AC Line Filtering Performance Electrochemical Capacitors. (2nd May 2014) - Nathan‐Walleser, Teressa; Lazar, Ion‐Matei; Fabritius, Martin; Tölle, Folke Johannes; Xia, Qi; Bruchmann, Bernd; Venkataraman, Shyam S.; Schwab, Matthias Georg; Mülhaupt, Rolf
<x xml:space="preserve">Abstract</x> A facile one‐step printing process by 3D micro‐extrusion affording binder‐free thermally reduced graphene oxide (TRGO) based electrochemical capacitors (ECs) that display high‐rate performance is presented. Key intermediates are binder‐free TRGO dispersion printing inks with concentrations up to 15 g L−1. This versatile printing technique enables easy fabrication of EC electrodes, useful in both aqueous and non‐aqueous electrolyte systems. The as‐prepared TRGO material with high specific surface area (SSA) of 593 m2 g−1 and good electrical conductivity of ≈16 S cm−1 exhibits impressive charge storage performances. At 100 and 120 Hz, ECs fabricated with TRGO show time constants of 2.5 ms and 2.3 ms respectively. Very high capacitance values are derived at both frequencies ranging from 3.55 mF cm−2 to 1.76 mF cm−2. Additionally, these TRGO electrodes can be charged and discharged at very high voltage scan rates up to 15 V s−1 yielding 4 F cm−3 with 50% capacitance retention. Electrochemical performance of TRGO electrodes in electrolyte containing tetraethyl ammonium tetrafluoroborate and acetonitrile (TEABF4‐ACN) yields high energy density of 4.43 mWh cm−3 and power density up to 42.74 kW cm−3, which is very promising for AC line filtering application and could potentially substitute state of the art electrolytic capacitor technology.